Acinar Cell-Derived Extracellular Vesicle MiRNA-183-5p Aggravates Acute Pancreatitis by Promoting M1 Macrophage Polarization Through Downregulation of FoxO1 - Tang, De-sheng; Cao, Feng; Yan, Chang-sheng; Cui, Ji-tao; Guo, Xiao-yu; Cheng, Long; Li, Le; Li, Yi-long; Ma, Jia-min; Fang, Kun; Gao, Lei; Ren, Nian-sheng; et al. (Frontiers in Immunology, 2022)
Acute pancreatitis (AP) is a common cause of a clinically acute abdomen. Crosstalk between acinar cells and leukocytes (especially macrophages) plays an important role in the development of AP. However, the mechanism that mediates the interaction between acinar cells and macrophages is still unclear. This study was performed to explore the role of acinar cell exosomes in the crosstalk between acinar cells and macrophages involved in the pathogenesis of AP. Exosomes derived from caerulein-treated acinar cells could induce macrophage infiltration and aggravate pancreatitis in an AP rat model. Further research showed that acinar cell-derived exosomal miR-183-5p led to M1 macrophage polarization by downregulating forkhead box protein O1(FoxO1), and a dual-luciferase reporter assay confirmed that FoxO1 was directly inhibited by miR-183-5p. In addition, acinar cell-derived exosomal miR-183-5p reduced macrophage phagocytosis. Acinar cells-derived exosomal miR-183-5p promoted the pancreatic infiltration of M1 macrophages and increased local and systemic damages in vivo. Subsequently, miR-183-5p overexpression in macrophages induced acinar cell damage and trypsin activation, thus further exacerbating the disease. Clinically, elevated miR-183-5p was found in serum exosomes and positively correlated with the severity of AP. Exosomal miR-183-5p might play an important role in the development of AP by facilitating M1 macrophage polarization, providing a new insight into the diagnosis and targeted management of pancreatitis.